MEMAKNAI PRAKTIK AKUNTANSI BAGI TOKO ONLINE - Zandra, Rosy Aprieza Puspita (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2018)
This study intends to examine the understanding of one of the online batik shops inPamekasan for accounting practices and their use in financial management at the batikshop